Management Supervision Strategy to Encourage the Implementation of Religious Moderation Values in the Digital Era - Minarni, Minarni (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to determine the supervision of Madrasah management in instilling the values of Religious Moderation in MAN 2 Bengkulu City.Methodology: The method used in this study is qualitative descriptive with a phenomenological approach. The research data sources are primary and secondary, and data collection techniques are conducted through observations, interviews, and documentation. The location of the research is in MAN 2, Bengkulu City.Main Findings: The study results show that the researcher found that the curriculum used already contains the values of religious moderation. The material is already content about tolerance and pluralism in line with the emphasis on character education in the curriculum, including tolerance, pluralism, and national values, at every level of education. Parents actively participate because parental involvement is essential in supporting the teaching of tolerance and pluralism in schools. Parents act as role models for children in instilling the values of tolerance, mutual respect, and appreciation for differences.Novelty/Originality of this study: Development of an information technology-based management supervision model to monitor the implementation of religious moderation values. The concept of "Digital Moderation" is a new approach to facing the challenges of the digital era, integrating the value of religious moderation with the principles of artificial intelligence. This research makes an academic contribution and offers concrete solutions to the challenges Islamic educational institutions face in building a moderate and competitive generation in the digital era.